2013
DOI: 10.1016/j.neuint.2012.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective properties of traditional Chinese medicinal herbal extracts in hydrogen peroxide challenged human U373 astroglia cells

Abstract: Munch, G. (2013). Cytoprotective properties of traditional Chinese medicinal herbal extracts in hydrogen peroxide challenged human U373 astroglia cells. Neurochemistry International: the journal for the publication of cellular and molecular aspects of neurochemistry, 62 (5), 522-529. Cytoprotective properties of traditional Chinese medicinal herbal extracts in hydrogen peroxide challenged human U373 astroglia cells AbstractAge is the leading risk factor for many of the most prevalent and devastating diseases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…While the neuroprotective activity was correlated with the antioxidant capacity of the extracts, two extracts ( Polygonum multiflorum and Rhodiola rosea ) with high anti-oxidant capacity lacked neuroprotective activity in the staurosporine assay and exhibited some neurotoxic activity when they were applied in the absence of staurosporine. These results complement our previous study reporting on the cytoprotective properties of these extracts in glial cells [15]. Interestingly, some extracts exhibited selective protection in neurons but not glia ( Polygonum cuspidatum ) or glia but less so in neurons ( P. multiflorum ).…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…While the neuroprotective activity was correlated with the antioxidant capacity of the extracts, two extracts ( Polygonum multiflorum and Rhodiola rosea ) with high anti-oxidant capacity lacked neuroprotective activity in the staurosporine assay and exhibited some neurotoxic activity when they were applied in the absence of staurosporine. These results complement our previous study reporting on the cytoprotective properties of these extracts in glial cells [15]. Interestingly, some extracts exhibited selective protection in neurons but not glia ( Polygonum cuspidatum ) or glia but less so in neurons ( P. multiflorum ).…”
Section: Introductionsupporting
confidence: 90%
“…Interestingly, some extracts exhibited selective protection in neurons but not glia ( Polygonum cuspidatum ) or glia but less so in neurons ( P. multiflorum ). Together, the data appear to support the traditional practice of combining multiple herbal medicines for the treatment of complex disorders [15]. The results of this study provide a justification for further testing of these herbal extracts in neurodegenerative animal models to assess their safety and effectiveness in vivo as a basis for subsequent clinical studies in humans.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Conventional treatment consists in relieving symptoms associated with ND, but due to side effects associated with these medicines, interest has been directed towards traditional herbal medicines (TMs) as a potential treatment. A number of herbal medicines have been used to complement the conventional drug therapies in the management of neurodegenerative diseases for centuries 6 . Many active pharmacological compounds from herbal medicines have been identified to be useful in treatment of ND.…”
Section: Introductionmentioning
confidence: 99%
“…Research showed that F. multiflora has potent antioxidative and cytoprotective properties [1], enhanced purgative effects, promoted diuresis and choleretic effects [2], and exerted a neuroprotective effect against glutamate-induced neurotoxicity [3]. 2,3,5,4'-tetrahydroxy stilbene-2-O-ß-Dglucoside (THSG) is an active component in F. multiflora, which possesses anti-hyperlipidemic [4], anti-oxidative, anti-inflammatory, endothelial-protective activities [5].…”
Section: Introductionmentioning
confidence: 99%